Mediating Role of Organizational Commitment on the Influence of Workload and Organizational Culture on Organizational Citizenship Behavior - Febry Rizky Al Fadilla Sitompul; Sri Rahayu (International Forum of Researchers and Lecturers, 2024)
The purpose of the study was to determine the direct and indirect influence of workload variables, organizational culture on organizational citizenship behavior through organizational commitment on employees of PT. Daihatsu Capella Medan. The type of research is associative causal and uses quantitative research methods. The population in this study were all employees at PT. Capella Medan Daihatsu totaling 78 people. The sampling method used the nonprobability sampling method with the census sampling technique. So the sample in this study was 78 employees at PT. Capella Medan Daihatsu. The results of the study are workload directly has a significant effect on organizational commitment at PT. Capella Medan Daihatsu. Organizational culture directly has a significant effect on organizational commitment at PT. Capella Medan Daihatsu. Workload directly has a significant effect on organizational citizenship behavior at PT. Capella Medan Daihatsu. Organizational culture directly has not significant effect on organizational citizenship behavior at PT. Capella Medan Daihatsu. Organizational commitment directly has a significant effect on organizational citizenship behavior at PT. Capella Medan Daihatsu. Workload indirectly has a significant effect on organizational citizenship behavior through organizational commitment at PT. Capella Medan Daihatsu. Organizational culture indirectly has a significant effect on organizational citizenship behavior through organizational commitment at PT. Capella Medan Daihatsu.